2013
DOI: 10.1186/1471-2458-13-96
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing practices among black primary care physicians in the United States

Abstract: BackgroundThe Centers for Disease Control and Prevention recommends routine HIV testing in all healthcare settings, but it is unclear how consistently physicians adopt the recommendation. Making the most of each interaction between black physicians and their patients is extremely important to address the HIV health disparities that disproportionately afflict the black community. The goal of this survey-based study was to evaluate the perceptions and practices of black, primary care physicians regarding HIV tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…2,4,5 Routine HIV testing with linkage to care is a key strategy for early diagnosis, treatment, and reduction of ongoing HIV transmission. Yet rates of routine HIV testing among providers remain suboptimal ( < 40% of providers surveyed reported routine HIV testing with their patients), 6 despite recommendations that providers in health care settings perform routine HIV testing for patients aged 13-64 years 7 or ages 15-65 years 8 and that annual HIV testing occur for persons at high risk of acquiring HIV. 7,8 Recent data suggest that more frequent HIV screenings every 3-6 months may be appropriate for some subgroups of young MSM who are at increased risk.…”
Section: Introductionmentioning
confidence: 82%
“…2,4,5 Routine HIV testing with linkage to care is a key strategy for early diagnosis, treatment, and reduction of ongoing HIV transmission. Yet rates of routine HIV testing among providers remain suboptimal ( < 40% of providers surveyed reported routine HIV testing with their patients), 6 despite recommendations that providers in health care settings perform routine HIV testing for patients aged 13-64 years 7 or ages 15-65 years 8 and that annual HIV testing occur for persons at high risk of acquiring HIV. 7,8 Recent data suggest that more frequent HIV screenings every 3-6 months may be appropriate for some subgroups of young MSM who are at increased risk.…”
Section: Introductionmentioning
confidence: 82%
“…7 In contrast, providers who perceive their patients to be at high risk of HIV perform more frequent testing. 34 Mentally ill individuals are more likely than others to engage in high-risk behaviors associated with HIV transmission, including unprotected sexual intercourse, injection drug use, and sex with multiple partners. 35,36 Recognition of these risk factors may prompt patients to seek and for providers to offer HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have shown that HIV testing rates are higher for patients receiving health services from obstetricians/gynecologists. [33][34][35] As others have discussed, during a routine gynecological exam, it may be easier to recommend HIV testing in the context of general screening for sexually transmitted infections since sexual activity is assumed. Pregnancy may also increase the likelihood of HIV testing, given that the CDC and the American College of Obstetrics and Gynecology recommend opt-out HIV testing for pregnant women.…”
Section: Compliance With Hiv Testing Laws -Kennedy Et Almentioning
confidence: 99%